ANALISIS POTENSI PEMANFAATAN TEKNOLOGI QRIS TERHADAP PENGURANGAN KETERGANTUNGAN UANG TUNAI DI INDONESIA - Bungsu S, Yahya Putra; Unda, Unda; Malia, Rizka; Purwaningsih, Vitriyani Tri; Mariska, Mega (Jurnal Ekonomi dan Bisnis (EK dan BI), 2024)
This study aims to investigate the implementation of the Quick Response Code Indonesian Standard (QRIS). Utilizing secondary data the research investigates how QRIS implementation affect the money supply in Indonesia. The method employed is a multiple linier regression time series analysis using monthly data from January 2021 to December 2023. The variables analyzed include the nominal value of QRIS transactions, Inflation, Interest rates and the money supply measured through official monetary statistics. The testing tools used are Stat 14 Software, which is utilized for resgression analysis and Hypothesis testing. The test conducted in this study include Normality Test, Autocorrelation Test, Heteroscedatisity Test and Multicollinearity test. The results indicate that QRIS transactions have a positive and significant impact on M1 in the short term. In the long term, QRIS transactions also have a positive and significants effect on M1. The study concluedes that QRIS transactions in Indonesian have not yet contributed to a reduction in the money supply. Keywords: Money Supply, QRIS Technology,Inflations, Interest rate